2016
DOI: 10.1021/acschembio.6b00720
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism for Isoform-Selective Inhibition of Acyl Protein Thioesterases 1 and 2 (APT1 and APT2)

Abstract: Post-translational S-palmitoylation directs the trafficking and membrane localization of hundreds of cellular proteins, often involving a coordinated palmitoylation cycle that requires both protein acyl transferases (PATs) and acyl protein thioesterases (APTs) to actively re-distribute S-palmitoylated proteins towards different cellular membrane compartments. This process is necessary for the trafficking and oncogenic signaling of S-palmitoylated Ras isoforms, and potentially many peripheral membrane proteins.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
134
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(146 citation statements)
references
References 26 publications
5
134
0
Order By: Relevance
“…This inhibitor concentration is ~4-times higher than the K i , suggesting ML349 is ready cell permeable and achieves equivalent inhibition in vitro and in living cells. ML348 had no significant effect on Scrib membrane localization, similar to an inactive ML349 derivative where the sulfone is reduced (Won et al, 2016). Importantly, Palmostatin B does not enhance Scrib perimeter localization to a higher level than ML349.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This inhibitor concentration is ~4-times higher than the K i , suggesting ML349 is ready cell permeable and achieves equivalent inhibition in vitro and in living cells. ML348 had no significant effect on Scrib membrane localization, similar to an inactive ML349 derivative where the sulfone is reduced (Won et al, 2016). Importantly, Palmostatin B does not enhance Scrib perimeter localization to a higher level than ML349.…”
Section: Resultsmentioning
confidence: 96%
“…Both APT1 and APT2 are annotated as protein de-palmitoylases (Tom and Martin, 2013), and are widely expressed and active across nearly all tissues (Bachovchin et al, 2010). Both enzymes are targets of several classes of covalent serine hydrolase inhibitors, including β-lactones (Dekker et al, 2010), triazole ureas (Adibekian et al, 2010c), and N -hydroxyhydantoin carbamates (Cognetta et al, 2015), as well as the reversible isoform selective piperazine amide inhibitors ML348 and ML349 (Adibekian et al, 2012; Davda and Martin, 2014; Won et al, 2016). The β-lactone inhibitor Palmostatin B is the most widely used APT inhibitor, and is primarily selective for both APT1 and APT2 at low micromolar concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…[36][37][38][39] The crystal structures of APT1 and APT2 have been determined, revealing an architecture containing a central structure made up of parallel β sheets, connected by loops and surrounded by α-helices. 38,40 Experimental evidence obtained in various laboratories (including ours) has indicated that both enzymes are mainly cytosolic with a highly hydrophilic character. 25,26,41,42 Recently, APT1 and APT2 were found to undergo palmitoylation on cysteine 2, [43][44][45] which was suggested to facilitate the steady-state membrane localization and function of these thioesterases.…”
Section: Protein S-acylationmentioning
confidence: 90%
“…APT1 and APT2 contain a catalytic triad made up of serine, histidine and aspartic acid, and also a glycine‐X‐serine‐X‐glycine motif, which is characteristic of the large family of α/β hydrolases and serine hydrolases . The crystal structures of APT1 and APT2 have been determined, revealing an architecture containing a central structure made up of parallel β sheets, connected by loops and surrounded by α‐helices . Experimental evidence obtained in various laboratories (including ours) has indicated that both enzymes are mainly cytosolic with a highly hydrophilic character .…”
Section: Protein S‐acylationmentioning
confidence: 92%
See 1 more Smart Citation